2019
DOI: 10.1080/07352166.2019.1565819
|View full text |Cite
|
Sign up to set email alerts
|

Mixed embeddedness and entrepreneurial activities of rural migrants in the host region: The case of Yuhuan City, China

Abstract: This study seeks to investigate how rural migrants from less developed areas survive the hurdles of starting businesses in the host region in China from the perspective of mixed embeddedness. Based on 40 interviews via a snowballing survey strategy in Yuhuan City, Zhejiang Province, it is shown that rural migrant workers (RMWs) create their own enterprises through social and institutional embeddedness. Rural migrants can benefit from social embeddedness, particularly by developing relationships with local entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Embeddedness relates to the qualitative facets and the nature of relationships (Andersson et al., 2005) where people choose to deal with those that they know well because of trustworthiness and mutual understanding formed by prior experiences (Lai, 2017). Mixed embeddedness refers to the embedding course of immigrant entrepreneurs in the social, economic and institutional settings of the host country, which helps immigrant entrepreneurs overcome barriers with regards to capital, labour, market information, protocols, and such like in the host countries (Kloosterman et al., 1999; Zhu et al., 2019). The choice of Lincolnshire is linked to the fact that the county typifies rural England since it is the second-largest county in England (Barnes and Cox, 2007), yet with fewer cities and urban areas and has critical issues with transport (Ward et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Embeddedness relates to the qualitative facets and the nature of relationships (Andersson et al., 2005) where people choose to deal with those that they know well because of trustworthiness and mutual understanding formed by prior experiences (Lai, 2017). Mixed embeddedness refers to the embedding course of immigrant entrepreneurs in the social, economic and institutional settings of the host country, which helps immigrant entrepreneurs overcome barriers with regards to capital, labour, market information, protocols, and such like in the host countries (Kloosterman et al., 1999; Zhu et al., 2019). The choice of Lincolnshire is linked to the fact that the county typifies rural England since it is the second-largest county in England (Barnes and Cox, 2007), yet with fewer cities and urban areas and has critical issues with transport (Ward et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Bagwell (2015) also suggested that TEFs can show nominal degrees of mixed-embeddedness in host countries, ranging from high to none. More recently, Zhu et al (2019) studied how rural migrants from less-developed areas survive the hurdles of starting businesses in China as the host region, albeit in a domestic setting. Finally, Solano (2020) employed the mixed-embeddedness perspective to study the growth of Moroccans' businesses in two European cities, Amsterdam and Milan.…”
Section: (Transnational) Mixed-embeddednessmentioning
confidence: 99%
“…The perspective of social embeddedness theory indicates that the migrants have new patterns of living by improved economics, which reconstruct social resources and networks among migrants and finally improve their social adaptations to local society (Bisignano and El-Anis, 2019). The process of social embeddedness reflects the process of local socialization, including social structure embeddedness such as the localization of economical living and family pattern, and social network embeddedness such as the extension of social network and the achievement of social integration (Zhu et al , 2019). Both social structure embeddedness and social network embeddedness improve the adaptation to local society and help migrants achieve the localization (Quan et al , 2019).…”
Section: Theoretical Framework Of the Social Embeddedness Theorymentioning
confidence: 99%
“…The second embeddedness step is the social network embeddedness, including social integration process and the extension of social networks (Quan et al , 2019). The third embeddedness is culture embeddedness, which is the result of economic and social embeddedness and in turn has impacts to the process of the entire social embeddedness (Zhu et al , 2019). Based on this theoretical framework, this study discusses the current situation of migrant workers in China from the perspective of economic embeddedness, social network embeddedness and culture embeddedness.…”
Section: Theoretical Framework Of the Social Embeddedness Theorymentioning
confidence: 99%